Issues of improving the implementation of tax obligations in Uzbekistan (Eurasian Research Bulletin, 2024)
In this article, the normative-legal basis of the tax legislation of Uzbekistan is studied, the main focus is on the tax legislation and the role of taxpayers' obligations. Also, conclusions were drawn on common problems, including the need to improve the enforcement of tax obligations and tax evasion, to make tax legislation and tax rules clearer and simpler. At the same time, some important reforms were studied, and scientific and practical conclusions and proposals were developed on foreign experience and its application in our country